Microbiota and COVID-19: Long-term and complex influencing factors - Gang, Jiaqi; Wang, Haiyu; Xue, Xiangsheng; Zhang, Shu (Frontiers in Microbiology, 2022)
The coronavirus disease 2019(COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2(SARS-CoV-2). According to the World Health Organization statistics, more than 500 million individuals have been infected and more than 6 million deaths have resulted worldwide. Although COVID-19 mainly affects the respiratory system, considerable evidence shows that the digestive, cardiovascular, nervous, and reproductive systems can all be involved. Angiotensin-converting enzyme 2 (AEC2), the target of SARS-CoV-2 invasion of the host is mainly distributed in the respiratory and gastrointestinal tract. Studies found that microbiota contributes to the onset and progression of many diseases, including COVID-19. Here, we firstly conclude the characterization of respiratory, gut, and oral microbial dysbiosis, including bacteria, fungi, and viruses. Then we explore the potential mechanisms of microbial involvement in COVID-19. Microbial dysbiosis could influence COVID-19 by complex interactions with SARS-CoV-2 and host immunity. Moreover, microbiota may have an impact on COVID-19 through their metabolites or modulation of ACE2 expression. Subsequently, we generalize the potential of microbiota as diagnostic markers for COVID-19 patients and its possible association with post-acute COVID-19 syndrome (PACS) and relapse after recovery. Finally, we proposed directed microbiota-targeted treatments from the perspective of gut microecology such as probiotics and prebiotics, fecal transplantation and antibiotics, and other interventions such as traditional Chinese medicine, COVID-19 vaccines, and ACE2-based treatments.